2003
DOI: 10.1002/path.1499
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BUB1 protein in gastric cancer correlates with the histological subtype, but not with DNA ploidy or microsatellite instability

Abstract: During mitosis, the spindle checkpoint delays the onset of anaphase until all chromosomes have attached properly to the mitotic spindle, preventing chromosome missegregation. BUB (budding uninhibited by benzimidazole) 1 is one of the key components of this checkpoint. BUB1 mutations are rare in cancer tissues and no mutations have been identified in gastric cancer. In mice, immunodepletion of BUB1 abolished the spindle checkpoint. Thus, aberrant expression of BUB1 protein could impair mitotic checkpoint functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…BCL6 was highly expressed in differentiated cancers and was remarkably reduced or absent in undifferentiated cancers. Previous studies of gastric cancers have found that genes such as BUB1, eRF3/GSPT1, and hCG-1 were correlated with histological type (Grabsch et al, 2004;Malta-Vacas et al, 2005;Liu et al, 2007). However, the precise mechanism of association between the expression of these genes and the histology of gastric cancer is not well understood.…”
Section: Discussionmentioning
confidence: 97%
“…BCL6 was highly expressed in differentiated cancers and was remarkably reduced or absent in undifferentiated cancers. Previous studies of gastric cancers have found that genes such as BUB1, eRF3/GSPT1, and hCG-1 were correlated with histological type (Grabsch et al, 2004;Malta-Vacas et al, 2005;Liu et al, 2007). However, the precise mechanism of association between the expression of these genes and the histology of gastric cancer is not well understood.…”
Section: Discussionmentioning
confidence: 97%
“…BRCA1, BRCA2, ATM, MLH1, and MSH2 immunohistochemistry was done on tissue microarrays constructed from the same series as described by Simon et al (33), sampling at random a minimum of three cores of 0.6-mm diameter from each tumor. Antigen retrieval, blocking procedures, and the modified ImmunoMax method used have previously been described (34). For further details of the immunohistochemical procedures, see Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The BubR1 insufficiency affects life span, aging-related aneuploidy, and senescence (39). Mutations of Bub1 and BubR1, along with several mitotic checkpoint genes, were rarely reported clinically (31,40,41). Up-regulation of checkpoint genes Bub1 and BubR1 was reported in several clinical studies on gastric (40) and colorectal malignancies with significantly shorter relapse-free survival rate (12).…”
Section: Discussionmentioning
confidence: 99%